1999
DOI: 10.1128/mcb.19.10.7203
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Signaling Pathways of the Insulin-Like Growth Factor 1 Receptor in Protection from Apoptosis

Abstract: The type 1 insulin-like growth factor receptor (IGF-1R), activated by its ligands, protects several cell types from a variety of apoptotic injuries. The main signaling pathway for IGF-1R-mediated protection from apoptosis has been previously elucidated and rests on the activation of phosphatidylinositol 3-kinase, Akt/protein kinase B, and the phosphorylation and inactivation of BAD, a member of the Bcl-2 family of proteins. In 32D cells (a murine hemopoietic cell line devoid of insulin receptor substrate 1 [IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
423
1
6

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 456 publications
(462 citation statements)
references
References 80 publications
32
423
1
6
Order By: Relevance
“…In 32D cells, high levels of expression of the IGF-IR result in di erentiation and eventually cell death (Valentinis et al, 1999b). Ectopic expression of IRS-1 inhibits di erentiation and promotes rapid growth (Valentinis et al, 1999b;Peruzzi et al, 1999). Indeed, the present experiments con®rm that the combined e ect of the IGF-IR and IRS-1 is to increase the aggressiveness of cells, as demonstrated by colony formation in soft agar and tumor formation in nude mice.…”
Section: Effect Of Irs-1 On the Growth Of Lncap Cells In Nude Micesupporting
confidence: 57%
“…In 32D cells, high levels of expression of the IGF-IR result in di erentiation and eventually cell death (Valentinis et al, 1999b). Ectopic expression of IRS-1 inhibits di erentiation and promotes rapid growth (Valentinis et al, 1999b;Peruzzi et al, 1999). Indeed, the present experiments con®rm that the combined e ect of the IGF-IR and IRS-1 is to increase the aggressiveness of cells, as demonstrated by colony formation in soft agar and tumor formation in nude mice.…”
Section: Effect Of Irs-1 On the Growth Of Lncap Cells In Nude Micesupporting
confidence: 57%
“…IGF1R signaling is a potent promoter of cell survival in a variety of cultured mammalian cells. [19][20][21] To test whether loss of IGF1R signaling leads to increased apoptosis in a developing vertebrate embryo, we measured the activity of caspase 3, an executioner caspase. Reducing IGF1R signaling resulted in a four-fold, highly significant increase in caspase 3 activities over controls and coinjection of the igf1r MOs along with igf1r mRNA reduced caspase 3 activities to the basal level (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, we found that daily addition of IGF2 increased apoptosis in beta cells and probably in their precursors in GK pancreatic rudiment, suggesting that the anti-apoptotic effect of IGF2 is deficient in embryonic GK pancreas. The main signalling pathway for the antiapoptotic effect of IGFs involves IGF1R, IRS1 and IRS2, phosphatidylinositol 3 kinase, AKT and Bclassociated death promoter (BAD) [43,44]. An anomaly in these antiapoptotic signalling pathways remains to be determined in embryonic GK pancreas.…”
Section: Discussionmentioning
confidence: 99%